A New Aortic Arch Dissection Classification: The Fuwai Classification - Qiu, Juntao; Luo, Xinjin; Wu, Jinlin; Pan, Wei; Chang, Qian; Qian, Xiangyang; Sun, Xiaogang; Wei, Bo; Zhang, Liang; Liu, Shen; Jiang, Wenxiang; Yu, Cuntao (Frontiers in Cardiovascular Medicine, 2021)
Abstract Background Aimed to describe a new aortic arch dissection (AcD) classification-Fuwai classification. And compared the characteristics among different types. Methods All AcD patients who underwent surgical procedures at Fuwai Hospital from 2010 to 2015 were included. AcD was divided into three types: Fuwai type Cp, Ct, and Cd. Type Cp defined as the innominate artery or combined with the left carotid artery involved. Type Cd defined as the left subclavian artery or combined with the left carotid artery involved. Besides type Cp and Cd, other AcD were defined as type Ct. Chi-square test was adopted for the pairwise comparison among the three types. Kaplan-Meier was used for long-term survival and free of reoperation analysis. Results 1063 AcD patients were enrolled from 2010 to 2015. 54 patients were type Cp, 832 type Ct, and 177 type Cd. The highest operation proportion of Cp, Ct and Cd were partial arch replacement, total arch replacement and TEVAR. The surgical mortality in type Ct was higher compared to type Cd (Ct vs Cd = 9.38% vs 1.69%, p < 0.01) and type Cp (Ct vs Cp = 9.38% vs 1.85%, p = 0.06). There was no difference in surgical mortality of type Cp and Cd (p = 0.93). There were no significant differences in the long-term survival rates (p =0.38) and free of aorta-related re-operations (p = 0.19). Conclusion The Fuwai classification is help to distinguish different AcD. Different AcD has different surgical mortality and operation methods, but they have similar long-term results.